Membrane dynamics of resting and internalin B‐bound MET receptor tyrosine kinase studied by single‐molecule tracking. Issue 9 (29th August 2017) - Harwardt, Marie‐Lena I. E.; Young, Phoebe; Bleymüller, Willem M.; Meyer, Timo; Karathanasis, Christos; Niemann, Hartmut H.; Heilemann, Mike; Dietz, Marina S.
Abstract : The human MET receptor tyrosine kinase contributes to vertebrate development and cell proliferation. As a proto‐oncogene, it is a target in cancer therapies. MET is also relevant for bacterial infection by Listeria monocytogenes and is activated by the bacterial protein internalin B. The processes of ligand binding, receptor activation, and the diffusion behavior of MET within the plasma membrane as well as its interconnections with various cell components are not fully understood. We investigated the receptor diffusion dynamics using single‐particle tracking and imaging fluorescence correlation spectroscopy and elucidated mobility states of resting and internalin B‐bound MET. We show that internalin B‐bound MET exhibits lower diffusion coefficients and diffuses in a more confined area in the membrane. We report that the fraction of immobile receptors is larger for internalin B‐bound receptors than for resting MET. Results of single‐particle tracking in cells treated with various cytotoxins depleting cholesterol from the membrane and disrupting the actin cytoskeleton and microtubules suggest that cholesterol and actin influence MET diffusion dynamics, while microtubules do not have any effect. Abstract : The human MET receptor tyrosine kinase contributes to vertebrate development and can be activated by the bacterial protein internalin B. We studied diffusion dynamics of resting and internalin B‐bound MET in living cells using single‐particle tracking and imaging fluorescence correlation spectroscopy. Exposure to various cytotoxins enables us to discuss the influences of actin, microtubules, and cholesterol on diffusion.